Estimation of Cooling Rate and Its Effect on Temperature Dependent Properties in GTA Welded High Carbon Steel Joints - Dutta, J; S, Narendranath (Review of Industrial Engineering Letters, 2014)
An elaborate study has been conducted in this article to estimate the cooling rate of the Gas Tungsten arc (GTA) welded steel butt joints of grade AISI 1090. The temperature dependent thermal parameters has been investigated in connection with developed rate of cooling. Experiment has been carried out ffto determine the thermal cycle formed along the longitudinal direction from weld bead. Implementing experimental temperatures, Adams empirical cooling rate correlation has incorporated to analyze rate of cooling. A correlation has been suggested in this study, derived from thick plate temperature distribution model. To find out the heat loss from the joint, Vinokurov’s empirical combined heat transfer coefficient has been utilized and with it has verified with conventional heat transfer coefficient based on convection and radiation. Cooling rate has been found out to be very rapid at z = 36mm to z = 108mm based on thick plate model and it has completely agreed with the variation of Adams correlation. At higher temperatures above 800ºC, heat loss due to radiation completely dominates the convection and lower temperatures convection heat loss influences much than radiation. Heat loss due to convection and radiation fully justified with the results produced based on cooling rate and rapid cooling near the fusion boundary exists only for 5s-10s.